Der Effizienz- und Intelligenzbegriff in der Lexikographie und künstlichen Intelligenz: kann ChatGPT die lexikographische Textsorte nachbilden? - Arias-Arias, Iván; Domínguez Vázquez, María José; Valcárcel Riveiro, Carlos (Lexikos, 2024)
Efficiency and Intelligence in Lexicography and Artificial Intelligence: Can ChatGPT Recreate the Lexicographical Text Type? By means of pilot experiments for the language pair German–Galician, this paper examines the concept of efficiency and intelligence in lexicography and artificial intelligence (AI). The aim of the experiments is to gain empirically and statistically based insights into the lexicographical text type ”dictionary article” in the responses of ChatGPT-3.5, as well as into the lexicographical data on which this chatbot was trained. Both quantitative and qualitative methods are used for this purpose. The analysis is based on the evaluation of the outputs of several sessions with the same prompt in ChatGPT-3.5. On the one hand, the algorithmic performance of intelligent systems is evaluated in comparison with data from lexicographical works; on the other hand, the ChatGPT data supplied is analysed using specific text passages of the aforementioned lexicographical text type. The results of this study not only help to evaluate the efficiency of this chatbot regarding the creation of dictionary articles, but also to delve deeper into the concept of intelligence, the thought processes and the actions to be carried out in both disciplines. Keywords: lexicography, AI, ChatGTP-3.5, dictionary article, concept of efficiency, concept of intelligence, lexicographical text type, training data, lexicographical data